2004
DOI: 10.1086/422896
|View full text |Cite
|
Sign up to set email alerts
|

Weak‐Lensing Mass Distributions for 24 X‐Ray Abell Clusters

Abstract: We use the weak gravitational lensing effect to study the mass distribution and dynamical state of a sample of 24 X-ray luminous clusters of galaxies (0.05 < z < 0.31) observed with the FORS1 instrument mounted on the VLT-Antu (Unit Telescope 1) under homogeneous sky conditions and subarsecond image quality. The galaxy shapes were measured in the combined V, I, R image after deconvolution with a locally determined point-spread-function, while the two-dimensional mass distributions of the clusters were computed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(144 citation statements)
references
References 64 publications
(60 reference statements)
13
127
1
2
Order By: Relevance
“…Several weak lensing models have been published for this cluster (Squires et al 1997;Cypriano et al 2004;Radovich et al 2008;Okabe et al 2011;Soucail 2012). The most direct link we can make between our strong lensing model and these weak lensing models comes from a comparison of the mass measured by weak lensing in the area covered by our model.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Several weak lensing models have been published for this cluster (Squires et al 1997;Cypriano et al 2004;Radovich et al 2008;Okabe et al 2011;Soucail 2012). The most direct link we can make between our strong lensing model and these weak lensing models comes from a comparison of the mass measured by weak lensing in the area covered by our model.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…To correct for the PSF smearing, we use the Im2shape software (Bridle et al 2002), which has already demonstrated its potential to recover the intrinsic shape of the galaxies (Cypriano et al 2004;Bardeau et al 2005Bardeau et al , 2007Limousin et al 2007a,b). Starting with a given model for the shape of each object, the code convolves it with the local estimate of the PSF.…”
Section: Object Selectionmentioning
confidence: 99%
“…It also avoids the noise induced by galaxies whose shape is badly estimated because they are too close to bright cluster galaxies (e.g. Cypriano et al 2004).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations